Is COVID-19 the Ideal Period for Boosting the Use of Impression Management in Annual Reports? - Ruksana Parvin (Journal of Accounting, Business and Management (JABM), 2026)
This paper’s goal is to compare impression management (IM) practices before and during Covid-19 by reviewing existing literature to ascertain whether Covid-19 is the ideal time for boosting the use of IM in annual reports (AR). 69 papers that were published between 1992 and June 2024 were chosen. We found that both profitable and unprofitable organizations always tend to demonstrate their lucrativeness through using defensive and assertive IM tactics. Though no statistically supported evidence indicates that Covid-19 is an ideal period for IM to increase, we notice that the explanation of content is different. Covid-19 is emotive content, which is used as a vital weapon of IM by exploiting emotional terms during Covid-19. 53% of papers identify that organizations use rhetorical manipulation in AR’s photos for purposefully displaying their care and emotion for employees during Covid-19. 47% of research found that Covid-19 is the ideal time to apply the IM attribution of performance strategy, where managers are motivated to retain their jobs or conceal the reality. While unsuccessful businesses blame Covid-19 to justify their inefficiencies, successful organizations strive to show their capability in overcoming the Covid-19 challenge. These results guide regulators to understand how businesses exploit Covid-19 to impress stakeholders.